1990
DOI: 10.1093/ije/19.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids and Colorectal Adenoma among Male Self-Defence Officials in Northern Kyushu, Japan

Abstract: Colorectal adenoma is regarded as a precursor lesion of adenocarcinoma. In view of the controversy on serum cholesterol and colorectal cancer, the risk of colorectal adenoma was examined in relation to serum total cholesterol, triglycerides and HDL-cholesterol. In the comparison of 88 men having adenoma and 1055 men with normal colonoscopy, there was no association between serum total cholesterol and colorectal adenoma. An increased risk of adenoma was observed at the highest quartile of triglycerides and at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Our results were consistent with those of previous studies that reported a positive association between serum triglycerides and colorectal adenoma [5][6][7][8][9][10]. The association was confirmed by dose-dependent relationships between serum levels of triglycerides and the number of adenomas, which is associated with the risk of colorectal cancer [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were consistent with those of previous studies that reported a positive association between serum triglycerides and colorectal adenoma [5][6][7][8][9][10]. The association was confirmed by dose-dependent relationships between serum levels of triglycerides and the number of adenomas, which is associated with the risk of colorectal cancer [11].…”
Section: Discussionsupporting
confidence: 93%
“…Most epidemiologic studies [5][6][7][8][9][10] have consistently demonstrated that serum levels of triglycerides are associated with the risk of colorectal adenoma, a precursor lesion of colorectal cancer [11]. Recently, an animal study reported that an age-dependent hyperlipidemic state along with a suppressed lipoprotein lipase, which catalyzes hydrolysis of triglycerides, occurs in Apc-deficient mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies were conducted in the USA (16,18,20,32,35,(37)(38)(39)(40) , one in Sweden (42) , five in Korea (6,9,10,22,27) , two in China (23,30) , eight in Japan (8,24,26,28,29,31,36,43) , one in Austria (41) and three in European countries (4,17,34) (Tables 1 and 2). Pooled analysis showed a significant association between serum TAG and CRN (n 29 studies; summary RR = 1·08; 95 % CI 1·05, 1·12, P < 0·00001; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies were conducted in the USA (20,39) , one in Germany (19) , three in Korea (9,10,22) and three in Japan (28,29,36) ( Table 2). The results from nine studies showed that serum TC had a significant association with risk of CRA (RR = 1·04; 95 % CI 1·01, 1·09, P = 0·02) and there was no significant heterogeneity among these studies (Q = 5·26, P value for heterogeneity = 0·73, I 2 = 0 %; Table 3).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation